Self-consistent positive streamer-leader propagation model based on Finite Element Method (FEM) and Voltage Distortion Method (VDM) - Ma, Ziwei; Jasni, Jasronita; Ab Kadir, Mohd Zainal Abidin; Azis, Norhafiz (Universiti Putra Malaysia, 2023)
Researchers have worked on positive leader propagation models and proposed different theoretical and numerical approaches. The charge simulation method (CSM) has traditionally been chosen to model the quasi-static electric field of each stage of leader propagation. The biggest drawback of the CSM is that the calculation is complicated and time-consuming when dealing with asymmetric electric field structures. On the contrary, the finite element method (FEM) is more suitable and reliable for solving electrostatic field problems with asymmetric and complex boundary conditions, avoiding the difficulties of virtual charge configuration and electric field calculation under complex boundary conditions. This paper modeled a self-consistent streamer-leader propagation model in an inverted rod-plane air gap based on FEM and the voltage distortion method (VDM). The voltage distortion coefficient was analyzed to calculate the streamer length and space charge. The physical dynamic process of the discharge was simulated with the help of COMSOL Multiphysics and MATLAB co-simulation technology. The results show that the initial voltage of the first corona is -1036 kV, close to the experiment value of -1052 kV. The breakdown voltage of -1369 kV is highly consistent with the experimental value of -1365 kV. The largest streamer length is 2.72 m, slightly higher than the experimental value of 2.3 m. The leader velocity is 2.43×104 m/s, close to the experiment value of 2.2×104 m/s. This model has simple calculations and can be used in complex electrode configurations and arbitrary boundary conditions without simplifying the model structure, making the model more flexible.